In Vivo Efficacy of Lacticaseibacillus rhamnosus L8020 in a Mouse Model of Oral Candidiasis - Rei Ito; Yuichi Mine; Yoshie Yumisashi; Reina Yoshioka; Misa Hamaoka; Tsuyoshi Taji; Takeshi Murayama; Hiroki Nikawa (Journal of Fungi, 2021)
Oral candidiasis presents with multiple clinical manifestations. Among known pathogenic Candida species, Candida albicans is the most virulent and acts as the main causative fungus of oral candidiasis. Novel treatment modalities are needed because of emergent drug resistance and frequent candidiasis recurrence. Here, we evaluated the ability of Lacticaseibacillus rhamnosus L8020, isolated from healthy and caries-free volunteers, to prevent against the onset of oral candidiasis in a mouse model. Mice were infected with C. albicans, in the presence or absence of L. rhamnosus L8020. The mice were treated with antibiotics and corticosteroid to disrupt the oral microbiota and induce immunosuppression. We demonstrated that oral consumption of L. rhamnosus L8020 by C. albicans-infected mice abolished the pseudomembranous region of the mouse tongue; it also suppressed changes in the expression levels of pattern recognition receptor and chemokine genes. Our results suggest that L. rhamnosus L8020 has protective or therapeutic potential against oral candidiasis, which supports the potential use of this probiotic strain for oral health management.